Kontribusi usahatani sayuran katuk (Sauropus androgynus(l).merr ) terhadap pendapatan petani di Desa Lubuk Rengas Kabupaten Banyuasin - Lisna Oktariani; Yeyen Emadia Putri (Jurnal Agrotek Ummat, 2023)
This study aims to determine the amount of costs incurred and income received by farmers in farming and how much the contribution of farming to household income of farmers in Lubuk Rengas Village, Rantau Bayur District, Banyuasin Regency. The research location was determined purposively (purposive) with the consideration that this location is one of the areas that carry out katuk vegetable farming activities using the intercropping method on chili plants. The sampling method was carried out by simple random sampling (simple random method) of 20 farmers from a total population of 30 farmers. Based on the results of data processing, the amount of production costs incurred by farmers in producing katuk vegetables is Rp. 11,983,450/Ha/year with revenues of Rp. 36,900,000/Ha/year and the income generated is Rp. 24,916,550/Ha/year. So it can be concluded that katuk vegetable farming does not make such a large contribution, it only contributes to the total farmer household income of 23.96%.